Evaluasi Kualitas Fisik Taman Kota Sebagai Ruang Terbuka Publik Di Kota Tanjung Balai - C A Oktavihusna; B Karsono; D Andriani (Cered Indonesia Institute, 2023)
City parks are one of the needs of urban communities, so city parks should be equipped with adequate facilities to improve the quality of the urban environment. Mutiara Selat Malaka Park is a public open space that can accommodate community activities intended for all groups, starting from children to adults, but the physical elements and facilities in Mutiara Selat Malaka Park have not fully paid attention to their quality, such as facilities whose condition can no longer be used because they are damaged and do not meet the standards. Based on the provisions on public open space, city parks need to be supported by the quality of physical elements and city park facilities that are good and adequate, so that they can accommodate all users. The purpose of this research is to find out the physical quality problems in the park that are ignored by the responsible party both from the availability of facilities and the condition of the quality of hardscape elements based on the standards of city park elements and facilities using the mapping analysis method, and the methods used in this research are qualitative research methods, through direct observation of activities, elements and facilities at Mutiara Selat Malaka Park.